Circular RNA DGKB Promotes the Progression of Neuroblastoma by Targeting miR-873/GLI1 Axis - Yang, Jiale; Yu, Leitao; Yan, Jinlong; Xiao, Yu; Li, Weiming; Xiao, Juhua; Lei, Jun; Xiang, Deng; Zhang, Shouhua; Yu, Xin (Frontiers in Oncology, 2020)
Accumulated evidences suggested that circular RNAs (circRNA) played critical roles in tumorigenesis and progression. To our knowledge, no study reported the function of circular RNA DGKB (circDGKB, circRNA ID: hsa_circ_0133622) on progression of neuroblastoma (NB). Here, we showed that circDGKB was upregulated in NB tissues compared to the normal dorsal root ganglia. Moreover, the expression level of circDGKB was negatively correlated with the survival rate of NB patients. Mechanically, overexpression of circDGKB promoted the proliferation, migration, invasion and tumorigenesis of NB cells, and reduced cell apoptosis, and vice versa. In addition, qRT-PCR and/or Western blot results showed that circDGKB overexpression inhibited the expression level of miR-873 and enhanced GLI1 expression. Moreover, miR-873 functioned an opposite role to circDGKB, and significantly weakened circDGKB role in promoting NB progression. Furthermore, GLI1 upregulation also rescued miR-873 role in inhibiting NB progression. In conclusion, our work proved that circDGKB promoted NB progression via targeting miR-873/GLI1 axis in vitro and in vivo. Our study provided a new target for NB treatment and indicated that circDGKB could act as a novel diagnostic marker for NB.